The stimulation mechanism of students’ entrepreneurial intention in entrepreneurship course: A trait activation theory perspective - Wu, Jun; Pan, Wenhao; Chen, Shuqiu; Deng, Baijun (Frontiers in Psychology, 2022)
This study examines the extent to which flow experience inhibits/enhances the effects of students' creativity on their entrepreneurial intentions. This study provides evidence to support the contention that flow experience moderates the relationship between creativity and entrepreneurial intention by reference to a field survey of 226 Chinese college students in six college classes. These findings reveal the process and mechanism by which creativity affects entrepreneurial intention and the associated psychological contingency factors.